ECONOMIC LIFE AND DEVELOPMENT OF BUKHARA EMIRATE - Abduraimova S. E. (Western European Studies, 2024)
This article provides information about the economic life of the Bukhara Emirate and the changes that have occurred in it, the growth of production, the opening of enterprises and factories.
Keywords: Bukhara Emirate; economy; agriculture